Design of an Android-Based Gerdcare Dietary Management System for Gerd Patients - Bunga Nila Kinanti; Matahari; Dian Nitari Ribanor Sabarudin (Academic Bright Collaboration, 2026)
Purpose - This study aimed to design and develop GERDCARE, an Android-based dietary management and health education application to support self-management among individuals with or at risk of Gastroesophageal Reflux Disease (GERD). Methods - A Research and Development approach using the ADDIE model was employed. A needs assessment involving 122 university students was conducted to identify GERD symptoms and dietary patterns as the basis for system development. The application was evaluated through content validation by a general practitioner and user testing involving 20 participants using the System Usability Scale (SUS). Finding - A total of 13.1% of respondents were identified as being at risk for GERD, while the average dietary pattern score was categorized as moderate (67.64%). The GERDCARE application integrates early GERD risk detection, health education, food and beverage recommendations, meal and medication reminders, and a doctor consultation module. Expert validation yielded a feasibility level of 95.56% (highly valid), while user testing demonstrated a SUS score of 78.00, classified as Good and Acceptable. Research Implications - GERDCARE supports dietary management and health education for individuals with GERD by integrating multiple self-management features within a single Android-based platform. Users identified as being at risk are advised to seek further consultation with qualified healthcare professionals. Originality - This study presents GERDCARE as an Android-based platform that distinctively integrates preliminary GERD risk screening, structured health education, dietary recommendations, behavior reminders, and a doctor consultation module within a single system an integration not found in existing fragmented mHealth solutions for GERD.